Road to Belém: Scaling biosolutions for soil health and climate action gains momentum ahead of COP30 - Edward-Uwadiale, Regina; Ojanji, Wandera (CGIAR System Organization, 2025)
This article highlights the inaugural Road to Belém webinar, a pre-COP30 dialogue series focusing on scaling biosolutions — biological and naturally derived approaches such as microbial inoculants and biofertilizers — to restore soil health, enhance climate resilience, and support sustainable food systems globally. With over 40 % of cultivated land degraded and soil health crucial for nearly all food production, participants including scientists, policymakers, innovators, and practitioners from across Africa, Latin America, and the UK discussed evidence, policy, and investment pathways to accelerate adoption. The blog emphasizes Brazil’s leadership in bioinputs regulation and scaling, insights from soil health monitoring, business model innovation, and locally tailored solutions from Kenya and elsewhere. It underscores five key shifts needed to scale biosolutions — from contextual design and new business models to evidence, regulation, and enabling environments — and sets the scene for subsequent sessions in the series leading up to COP30 in Belém, Brazil, where soil health is a central theme in climate action dialogues.